LIVING TOGETHER WITH LGBT PEOPLE IN INDONESIA - Umar, Subehan Khalik (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2019)
Indonesia as the country with the most Muslim population in the world faced the challenge of placing LGBT actors in the state-citizen structure. The teachings of Islam expressly reject the LGBT Act, while the State is obliged to present in advocating the rights of LGBT actors for the reasons for enforcing human rights. In the meantime, LGBT actors still have no proper treatment and are vulnerable to discrimination, so the LGBT community seems to have no right to return to repentance. Islam as a religion that has the value of humanity, on the one hand, opened a wide path for the perpetrator to return to the way of God and the other side affirmed that LGBT behavior is the thing forbidden. This research is a juridical-normative study with a theological-normative approach (Syar'i), consisting of research on principles, systematics, and the synchronization of laws using Islamic law to approach objects. The research aims to formulate a new approach to LGBT actors to avoid discrimination and rediscover the path of repentance. The study found that structured efforts to approach LGBT actors will open up opportunities for them to repent and to those who wish to remain standing on their status, can be protected by regulatory Indonesian law has ratified UDHR and partial UDHR (Cairo Declaration)..